When Prevention is Not Enough: Students' Perception of Bullying and School-Wide Positive Behavior Interventions and Supports. (November 2019) - Gage, Nicholas A.; Rose, Chad A.; Kramer, Dennis A.
Bullying continues to be a major concern in U.S. schools and is the focus of myriad prevention and intervention efforts. Researchers have recently cited school-wide positive behavior interventions and supports (SWPBIS) as a prevention framework for reducing school-based bullying. Therefore, we examined the effect of universal SWPBIS implemented with fidelity on students' self-report of bullying victimization. We used school-level propensity score matching to compare 76, 248 students' self-report of bullying victimization in 118 schools that implemented SWPBIS with fidelity and 118 matched comparison schools. Random-effects regression models found no statistically significant difference between treatment groups on students' self-report of bullying victimization. Recommendations and limitations are discussed.